(untitled) (The Review of Diabetic Studies, 2025)
Background: Saudi Red Crescent Authority (SRCA) paramedics are frequently exposed to critical incidents and traumatic situations that may significantly impact their mental health and well-being. Understanding the psychological consequences and coping strategies employed by these first responders is crucial for developing appropriate support systems. Objectives: To examine the prevalence of psychological distress and post-traumatic stress disorder (PTSD) among Saudi paramedics, identify effective coping mechanisms, and assess the role of cultural and religious factors in managing stress. Methods: A cross-sectional study design involving SRCA paramedics across multiple regions of Saudi Arabia. Data collection includes standardized psychological assessment tools, semi-structured interviews, and demographic questionnaires. Expected Outcomes This research aims to provide evidence-based recommendations for mental health support programs tailored to the Saudi cultural context.